2021
DOI: 10.1038/s41467-021-25718-w
|View full text |Cite
|
Sign up to set email alerts
|

Non-fullerene acceptor organic photovoltaics with intrinsic operational lifetimes over 30 years

Abstract: Organic photovoltaic cells (OPVs) have the potential of becoming a productive renewable energy technology if the requirements of low cost, high efficiency and prolonged lifetime are simultaneously fulfilled. So far, the remaining unfulfilled promise of this technology is its inadequate operational lifetime. Here, we demonstrate that the instability of NFA solar cells arises primarily from chemical changes at organic/inorganic interfaces bounding the bulk heterojunction active region. Encapsulated devices stabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
158
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 184 publications
(160 citation statements)
references
References 49 publications
1
158
0
1
Order By: Relevance
“…[ 24 ] By comparing the stability difference of the IT‐4F cells with different ZnO interlayer, we recently proved that photon generated hydroxyl radicals on the ZnO surface is the chemical reactive species that causes the breaking of the C═C bonds. [ 25 ] With the better understanding on the detailed degradation mechanism of the NFA cells, methods to improve device stability, including blending with fullerene molecules, [ 26 ] surface treatment with Lewis acids, [ 27 ] a thin PEI layer, [ 28 ] or a self‐assembled monolayer [ 29 ] were reported, supporting the proposed degradation mechanism. Despite these excellent research works in improving the stability of the cells, these cells showed lower initial efficiencies less than the optimized cell performance, and most of the cells showed a PCE lower than 15%.…”
Section: Introductionmentioning
confidence: 88%
“…[ 24 ] By comparing the stability difference of the IT‐4F cells with different ZnO interlayer, we recently proved that photon generated hydroxyl radicals on the ZnO surface is the chemical reactive species that causes the breaking of the C═C bonds. [ 25 ] With the better understanding on the detailed degradation mechanism of the NFA cells, methods to improve device stability, including blending with fullerene molecules, [ 26 ] surface treatment with Lewis acids, [ 27 ] a thin PEI layer, [ 28 ] or a self‐assembled monolayer [ 29 ] were reported, supporting the proposed degradation mechanism. Despite these excellent research works in improving the stability of the cells, these cells showed lower initial efficiencies less than the optimized cell performance, and most of the cells showed a PCE lower than 15%.…”
Section: Introductionmentioning
confidence: 88%
“…Recently, Forrest et al 94 tested several modification/buffer materials for enhancing device reliability ( Fig. 22a ).…”
Section: Strategies To Suppress Photochemical Reactionsmentioning
confidence: 99%
“…Polymer solar cells (PSCs) have attracted extensive research attention and achieved rapid development in recent years due to their advantages of light weight, flexibility and feasibility of roll-to-roll process. [1][2][3][4][5][6] Active layer materials with bulk heterojunction (BHJ) structure formed by mechanical blending are important components of PSCs, which are usually composed of p-type polymer electron donors and ntype small molecule or polymer electron acceptors. [7][8][9] In the past few years, the power conversion efficiency (PCE) of PSCs has been boosted from 10 % to over 18 % because of the rapid development of various non-fullerene small molecular acceptors (NFSMAs) and polymer donors.…”
Section: Introductionmentioning
confidence: 99%